2021
DOI: 10.1080/1828051x.2021.1921628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary saffron (Crocus sativus) petal extract on growth performance, blood biochemical indices, antioxidant balance, and immune responses of broiler chickens reared under heat stress conditions

Abstract: Piray (2021) Effect of dietary saffron (Crocussativus) petal extract on growth performance, blood biochemical indices, antioxidant balance, and immune responses of broiler chickens reared under heat stress conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is reported that, generally, 158,000-300,000 flowers are necessary to produce 1 kg of spice [5], with about 78 kg of petals discarded per 1 kg of stigmas [6,7]. Saffron petals are mainly used for animal feed or as natural dye for fibers [8,9]. However, it is noteworthy that saffron petals are rich in many antioxidant compounds [10], such as phenols, anthocyanins, and flavonoids [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that, generally, 158,000-300,000 flowers are necessary to produce 1 kg of spice [5], with about 78 kg of petals discarded per 1 kg of stigmas [6,7]. Saffron petals are mainly used for animal feed or as natural dye for fibers [8,9]. However, it is noteworthy that saffron petals are rich in many antioxidant compounds [10], such as phenols, anthocyanins, and flavonoids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Heterophils increased in summer at 42 days old, and the higher H/L ratio observed in winter in the LO treatment, at 28 days old, as a result of heterophilia, was contrary to the findings of Osti et al [ 32 ], whereby the H/L ratio was greater during summer, in accordance with Sanchez-Casanova et al [ 13 ], who found a higher H/L ratio in low-density treatments in winter, and Rajkumar et al [ 33 ], whose findings demonstrated a lower H/L ratio in summer. An increase in the H/L ratio is commonly observed during mild to moderate stress [ 34 , 35 ] and is also associated with elevated serum corticosterone concentrations [ 36 ]. Multiple stressors can increase this ratio such as fearfulness and heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions had been drawn from many in vivo experiments. Dietary administration of saffron petal extracts to heat-stressed broiler chickens enhanced the plasma concentration of SOD, GPx, as well as total antioxidant capacity, while reducing the levels of MDA . Similarly, after administration of saffron petal extracts, CAT, SOD, and MDA levels in isoniazid-rifampicin (INH-RIF) treated rats were normalized .…”
Section: Biological Activities Of Saffron Byproductsmentioning
confidence: 98%
“…Dietary administration of saffron petal extracts to heat-stressed broiler chickens enhanced the plasma concentration of SOD, GPx, as well as total antioxidant capacity, while reducing the levels of MDA. 59 Similarly, after administration of saffron petal extracts, CAT, SOD, and MDA levels in isoniazidrifampicin (INH-RIF) treated rats were normalized. 47 Alipour et al 60 found that subcutaneous injection or oral administration of 25 mg/kg of saffron petal extract resulted in higher SOD and GPx activities and lower triglyceride levels in plasma than the control group; moreover, the GPx activity in kidney and heart was affected by the treatment, and the SOD activity in kidney was also affected.…”
Section: •−mentioning
confidence: 99%